Trade and Financial Sector Reforms : Interactions and Spillovers - Taylor, Ashley (2012)
The allocation of production across firms is a potentially important explanation of the productivity gap between rich and poor economies. Reforms to trade policy and the domestic financial sector are often both key elements of policy packages aimed at reducing productive distortions. However, the impact of each reform in reallocating production within an economy is usually analyzed independently. This paper asks how do such general equilibrium effects of trade and domestic financial sector reforms interact in terms of their effects on productivity, wages and utility. Motivated by recent firm-level studies, I add two-way linkages between firms production and exporting decisions and their financial constraints to a general equilibrium heterogeneous firm trade model. The interaction effects between reforms appear qualitatively important. Trade and domestic financial sector reforms have complementary effects on the average productivity and size of domestic producers. However, if much reallocative work has already been done through a well-functioning financial sector, the marginal benefits of trade liberalisation for wages and household utility are reduced. Improvements in the ability to use exports as pledgeable collateral enhance both the wage and productivity effects of trade reforms. The model also highlights the potential for financial sector reforms in one economy to be exported via the trade channel, affecting decisions to produce or export in the foreign economy and putting downward pressure on foreign real wages.